Interpreting the relationships between TOEFL iBT scores and GPA: Language proficiency, policy, and profiles. (April 2018) - Ginther, April; Yan, Xun
This study examines the predictive validity of the TOEFL iBT with respect to academic achievement as measured by the first-year grade point average (GPA) of Chinese students at Purdue University, a large, public, Research I institution in Indiana, USA. Correlations between GPA, TOEFL iBT total and subsection scores were examined on 1990 mainland Chinese students enrolled across three academic years (N2011 = 740, N2012 = 554, N2013 = 696). Subsequently, cluster analyses on the three cohorts' TOEFL subsection scores were conducted to determine whether different score profiles might help explain the correlational patterns found between TOEFL subscale scores and GPA across the three student cohorts. For the 2011 and 2012 cohorts, speaking and writing subscale scores were positively correlated with GPA; however, negative correlations were observed for listening and reading. In contrast, for the 2013 cohort, the writing, reading, and total subscale scores were positively correlated with GPA, and the negative correlations disappeared. Results of cluster analyses suggest that the negative correlations in the 2011 and 2012 cohorts were associated with a distinctive Reading/Listening versus Speaking/Writing discrepant score profile of a single Chinese subgroup. In 2013, this subgroup disappeared in the incoming class because of changes made to the University's international undergraduate admissions policy. The uneven score profile has important implications for admissions policy, the provision of English language support, and broader effects on academic achievement.